Land compensation gap for the resettlement of the indigenous communties in Bakun hydroelectric Dam - Wen, Chiat Lee; Viswanathan, K. Kuperan; Ali, Jamal (Universiti Malaysia Sarawak, 2016)
Land compensation arising from relocation is a contested issue due to a lack of agreement on the levels of compensation by settlers.The effects of use values and non-use values on land compensation gap in Bakun Hydroelectric Dam in Sarawak, Malaysia are examined in this study.Multinomial Logit econometric estimators are used to examine the land compensation gap experienced by 379 settlers resettled as a result of the development project.The relationship between use values and non-use values in determining the land compensation gap is presented in the study.The gap is important in determining the satisfaction of settlers with regard to relocation.The findings can be used for better formulation of compensation policies in the case of large development projects.